A new version of the convexification method for a 1D coefficient inverse problem with experimental data. (21st September 2018) - Klibanov, Michael V; Kolesov, Aleksandr E; Sullivan, Anders; Nguyen, Lam
Abstract: A new version of the convexification method is developed analytically and tested numerically for a 1D coefficient inverse problem in the frequency domain. Unlike the previous version, this one does not use the so-called 'tail function', which is a complement of a certain truncated integral with respect to the wave number. Globally strictly convex cost functional is constructed with the Carleman weight function. Global convergence of the gradient projection method to the correct solution is proved. Numerical tests are conducted for both computationally simulated and experimental data.